2008
DOI: 10.1007/s00467-008-0751-z
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of phosphate homeostasis by the phosphatonins and other novel mediators

Abstract: A variety of factors regulate the efficiency of phosphate absorption in the intestine and phosphate reabsorption in kidney. Apart from the well-known regulators of phosphate homeostasis, namely parathyroid hormone (PTH) and the vitamin D-endocrine system, a number of peptides collectively known as the "phosphatonins" have been recently identified as a result of the study of various diseases associated with hypophosphatemia. These factors, fibroblast growth factor 23 (FGF-23), secreted frizzled-related protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(61 citation statements)
references
References 80 publications
0
58
0
2
Order By: Relevance
“…The current view is that, loss of PHEX function probably results in accumulation of phosphatonins which are circulating factors that regulate phosphate homeostasis and mineralization of bone. FGF23 [7], matrix extracellular phosphoglycoprotein (MEPE) [8], frizzled related protein 4 (FRP-4) [9] and FGF7 are the putative phosphatonins [10,11].…”
Section: (Enpp1) Genesmentioning
confidence: 99%
“…The current view is that, loss of PHEX function probably results in accumulation of phosphatonins which are circulating factors that regulate phosphate homeostasis and mineralization of bone. FGF23 [7], matrix extracellular phosphoglycoprotein (MEPE) [8], frizzled related protein 4 (FRP-4) [9] and FGF7 are the putative phosphatonins [10,11].…”
Section: (Enpp1) Genesmentioning
confidence: 99%
“…In hyperphosphatemic states, elevated phosphate and FGF23 concentrations may inhibit 1-a hydroxylase (16).…”
Section: Introductionmentioning
confidence: 99%
“…Fast foods or processed foods have high energy density and also frequently contain a large amount of P i as a food additive. Recent epidemiological studies have suggested that a high dietary P i intake can be associated with increased cardiovascular risk and other metabolic disorders.P i is an essential nutrient that significantly affects skeletal formation, energy metabolism, and intracellular signaling (43,45). P i homeostasis is regulated by the absorption of P i in the intestine, bone formation/resorption, and reabsorption of P i in the kidney.…”
mentioning
confidence: 99%
“…P i is an essential nutrient that significantly affects skeletal formation, energy metabolism, and intracellular signaling (43,45). P i homeostasis is regulated by the absorption of P i in the intestine, bone formation/resorption, and reabsorption of P i in the kidney.…”
mentioning
confidence: 99%